Aleppo and its hinterland in the Ottoman period = Alep et sa province à l'époque ottomane - Winter, Stefan; Ade, Mafalda (Social, economic and political studies of the Middle East and Asia, 2020)
Front Matter -- Copyright Page -- Préface -- List of Illustrations / liste d’illustrations -- Les Turkmènes d’Alep à l’époque ottomane (1516–1700) /Enver Çakar -- Armenians in the Production of Urban Space in Early Modern Judayda, Aleppo /Elyse Semerdjian -- Patterns of Leadership in the Guilds of 17th-Century Aleppo /Charles L. Wilkins -- Alep et l’émirat du désert (çöl beyliği) au xviie–xviiie siècle /Stefan Winter -- Halabis and Foreigners in Aleppo’s Mediterranean Trade: The Role of Levantine Merchants in Eighteenth-Century Commercial Networks /Mary Momdjian -- The Millet Wars in Aleppo, 1726–1821: An Ottoman perspective /Bruce Masters -- Antioche sous l’occupation égyptienne (1832–1840) : l’émergence d’un centre de pouvoir militaire et modernisateur /Sylvain Cornac -- L’innovation judiciaire dans l’Empire ottoman : L’établissement d’un tribunal de commerce à Alep au milieu du xixe siècle /Mafalda Ade -- Disciplining Disobedient Subjects: The Punishment of Aleppo’s Insurgents in 1850 as a Contentious Issue /Feras Krimsti -- Les consuls Picciotto et Poche, intermédiaires des intérêts belges à Alep (1855–1914) /Nicolas Jodoin -- Entre réseaux régional et transrégional : La Mawlawiyya dans la province d’Alep au xixe siècle /Stefan Knost -- Back Matter -- Index.